Paddling machine for kayaking sport: biomechanical tests and benefit analysis - Voronov, A.; Kvashuk, P.; Malkin, R.; Kotelevskaya, N. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to find to most beneficial individual paddling machine settings for the special strength training.